2001
DOI: 10.1007/bf03043036
|View full text |Cite
|
Sign up to set email alerts
|

Epibenthic diversity in the North Sea

Abstract: In 1999 the epibenthic fauna of the North Sea was investigated using the 3rd quarter 'International Bottom Trawl Survey' of five European countries. Altogether 241 stations were sampled covering 143 ICES rectangles. The objectives of the projects were (i) to analyse epibenthic diversity patterns in the North Sea, (ii) to identify the spatial distribution of faunal communities and (iii) to relate environmental factors as well as fishing effort to species diversity. Epibenthic fauna was clearly divided between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…The different durations of the 3 benthos surveys (10, 3 and 1 yr) may also have affected the comparison; the 1 yr survey in 2000, although covering more stations than any of the other surveys, may be less representative for the end of the century than the accumulated 10 yr survey at the beginning of the century. However, studies from 1996 and 1999 confirm the epibenthos patterns found in 2000 (Jennings et al 1999a, Zühlke et al 2001. Despite these limitations in the quality of data, it was possible to establish general temporal trends for the development in fishing and for changes in the epibenthos, which provide arguments for a possible link between the two.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The different durations of the 3 benthos surveys (10, 3 and 1 yr) may also have affected the comparison; the 1 yr survey in 2000, although covering more stations than any of the other surveys, may be less representative for the end of the century than the accumulated 10 yr survey at the beginning of the century. However, studies from 1996 and 1999 confirm the epibenthos patterns found in 2000 (Jennings et al 1999a, Zühlke et al 2001. Despite these limitations in the quality of data, it was possible to establish general temporal trends for the development in fishing and for changes in the epibenthos, which provide arguments for a possible link between the two.…”
Section: Discussionmentioning
confidence: 95%
“…They found changes in the benthic community composition in 3 of the rectangles, concurrent with the mechanization of the fishing fleet. Quantitative benthos data for the entire North Sea were not recorded before the late 1970s; systematic benthos surveys were carried out from 1982to 1987(Dyer et al 1983, Frauenheim et al 1989, Dann & Harding 1992, Künitzer et al 1992, Jennings et al 1999a, Zühlke et al 2001, Callaway et al 2002. However, Stein et al (1990) reconstructed epibenthos records from historical specimens at the Zoological Museum in Kiel, Germany, which had been collected over the years 1902 to 1912 at a wide range of locations throughout the North Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Reiss et al (2010), defined the species as characteristic of the northern North Sea. It was also detected in the IBTS cruises in 1999 (Zühlke et al 2001). The species seems to be less abundant in the southern North Sea, and there have been no reports from the Dogger Bank so far.…”
Section: Warm Water Speciesmentioning
confidence: 94%
“…Subsequently, several studies of the epibenthos were performed covering the whole North Sea (Dyer et al 1983;Frauenheim et al 1989;Jennings et al 1999;Zühlke et al 2001;Callaway et al 2002Callaway et al , 2007Reiss et al 2010). Rees et al (1999) compared benthic in-and epifauna of an even larger research area, including parts of the North Sea, the English Channel, the Celtic and the Irish Sea in a period from 1992 to 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Daan et al (1990) highlighted the importance to analyse fish communities instead of single commercial species to understand how the North Sea ecosystem functions. Since the beginning of such investigations, effort increased to analyse spatial community structure of fish (Greenstreet and Hall 1996;Ehrich et al 2009), benthic infauna (Duineveld et al 1991;Heip et al 1992;Künitzer et al 1992;Kröncke et al 2011) and benthic epifauna (Frauenheim et al 1989;Jennings et al 1999;Zühlke et al 2001) on a North Sea wide scale. However, similarities and the interrelationships in community structure between these faunal components were only recently studied, for example by Callaway et al (2002) and Reiss et al (2010).…”
Section: Introductionmentioning
confidence: 99%